Menegakkan Ham dan Mempertahankan Nilai Pancasila Dalam Masyarakat - Dwi Anugrah Prasetya; Ellocya Sembiring; Santia Santia (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This article discusses how to uphold human rights values ​​in Indonesian society based on Pancasila. The Pancasila ideology is seen as the basis of the Indonesian state because it contains several principles, such as the principles of divinity, humanity, nationality, sovereignty and social justice. Pancasila values ​​must be implemented in upholding human rights in society, taking into account the principles that have been previously established. Human rights in Indonesia are regulated by Pancasila and the 1945 Constitution. Implementation of human rights requires efforts from the government, non-governmental organizations and society to create an environment that supports respect for human dignity. Handling issues related to human rights and Pancasila values ​​is required with an inclusive approach and constructive dialogue. This article aims to discuss how human rights values ​​can be implemented in Indonesian society based on Pancasila. Apart from that, the article also aims to highlight the importance of implementing the noble values ​​of Pancasila in upholding human rights in Indonesia. The research method used in this article is text analysis and interpretation of human rights values, Pancasila ideology, the Basic Laws of the Republic of Indonesia, and implementation of noble values ​​of Casila in upholding human rights in Indonesia. The importance of implementing the noble values ​​of Pancasila in upholding human rights in Indonesia is also emphasized, by involving the government, non-governmental organizations and society in creating an environment that supports respect for human dignity. An inclusive approach and constructive dialogue are also considered important in dealing with issues related to human rights and Pancasila values.